Interest Arbitration in Ontario Hospitals: Result of an Attitude Survey of Union and Management Officials - Andiappan, P.; Cattaneo, R.; Murphy, John (Relations industrielles / Industrial Relations, 1984)
The study focuses on the perceptions that union and management officials have of interest arbitration in Ontario hospitals.